New Directions for Thinking about the Bible and Nonhuman Animals: A Review of Works by Peter Atkins, Dong Hyeon Jeong, and Saul Olyan - Millar, Suzanna (Vetus Testamentum, 2024)
Three new monographs have appeared in 2023 that explore the Bible and nonhuman animals: Peter Joshua Atkins, The Animalising Affliction of Nebuchadnezzar in Daniel 4: Reading Across the Human-Animal Boundary (London: T&T Clark, 2023; pp. xiv + 260); Dong Hyeon Jeong, Embracing the Nonhuman in the Gospel of Mark (Atlanta: SBL Press, 2023; pp. xii+177); Saul M. Olyan, Animal Rights and the Hebrew Bible (New York: OUP, 2023; pp. xii+144). This review brings these books into conversation, suggesting six questions that they grapple with and which might stimulate further research.